(untitled) (Experimental biology, 2015)
Сomposition of the storage proteins of glutenin on productive and high-protein content in grain on samples of M4 mutant lines of spring wheat (Triticum aestivum L.) from the created mutant collection on the genetic basis of grades and Jenis by exposure to different doses of gamma radiation is determined